2019
DOI: 10.1186/s13071-019-3675-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative iTRAQ-based quantitative proteomic analysis of the Chinese grass shrimp (Palaemonetes sinensis) infected with the isopod parasite Tachaea chinensis

Abstract: Background Although parasitic isopods can negatively affect the reproduction and ingestion of several commercially important crustaceans, little is known regarding the mechanisms that underlie these effects. Methods In the present study, the iTRAQ (isobaric tags for relative and absolute quantification) approach was applied to identify differentially expressed proteins in the Chinese grass shrimp Palaemonetes sinensis infected with the parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The salinity tolerance of other isopod species, such as Sphaeroma serratum , which usually inhabit coastal marine or brackish waters, has been studied, and the results showed that S. serratum is euryhaline, with lower and upper limits of ~2‰ and 74‰, respectively 25 . Tachaea chinensis not only has a strong salinity tolerance in different regions, but also survives in freshwater environments such as rivers and rice fields 26,27 . Although the salinity adaptation mechanisms of T. chinensis are unclear, these abilities are important for the adaptation of the species to different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The salinity tolerance of other isopod species, such as Sphaeroma serratum , which usually inhabit coastal marine or brackish waters, has been studied, and the results showed that S. serratum is euryhaline, with lower and upper limits of ~2‰ and 74‰, respectively 25 . Tachaea chinensis not only has a strong salinity tolerance in different regions, but also survives in freshwater environments such as rivers and rice fields 26,27 . Although the salinity adaptation mechanisms of T. chinensis are unclear, these abilities are important for the adaptation of the species to different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have assumed that isopod parasites can feed on fish blood or crustacean hemolymph, comparable to an “aquatic mosquito” (Wilson, 2008; Manship et al, 2012; Smit et al, 2014; Nagler et al, 2017). We previously found that hemocyanin in P. sinensis is significantly downregulated following parasitism by T. chinensis (Li et al, 2019). The present results indicate that hemocyanin in T. chinensis was significantly upregulated after parasitism, suggesting a role in obtaining hemolymph from P. sinensis .…”
Section: Discussionmentioning
confidence: 96%
“…After attacking its host, this isopod invariably remains attached until either the shrimp dies or another shrimp comes within close proximity. Over the past 2 years, T. chinensis has been shown to parasitize over 80% of aquacultured Palaemonetes sinensis (Li et al, 2018) and 90% of Exopalaemon carinicauda (Li et al, 2019). Additional research on isopod parasitization mechanisms is necessary to develop effective methods of control for use in shrimp aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were treated with vehicle, peptides PW5, and WN5 for 48 h, and added with tetracycline for another 72 h. Then, we collected the cells using PBS to obtain the proteins for detection. The further procedures including protein digestion, iTRAQ labeling, strong cation exchange (SCX) fractionation and LC-MS/MS analysis were conducted by BGI Company according to previous literatures [16,17].The proteins in the Model group (vehicle) were labeled with reagent 126, 127N and 127C, whereas those in the PW5-treated group were labeled with reagent 128N, 128C, and 129N, and the WN5-treated group were labeled with reagent 129C, 130N and 130C. After LC-MS/MS analysis, the raw files were analyzed by using Proteome Discover v.1.4 software.…”
Section: Proteomics Analysismentioning
confidence: 99%